Multiple 2D Phase Transformations in Monolayer Transition Metal Chalcogenides - Hong, Jinhua; Chen, Xi; Li, Pai; Koshino, Masanori; Li, Shisheng; Xu, Hua; Hu, Zhixin; Ding, Feng; Suenaga, Kazu (Advanced materials (Weinheim), 2022)
Phase transformation lies at the heart of materials science because it allows for the control of structural phases of solids with desired properties. It has long been a challenge to manipulate phase transformations in crystals at the nanoscale with designed interfaces and compositions. Here in situ electron microscopy is employed to fabricate novel 2D phases with different stoichiometries in monolayer MoS2 and MoSe2. The multiphase transformations: MoS2 → Mo4S6 and MoSe2 → Mo6Se6 which are highly localized with atomically sharp boundaries are observed. Their atomic mechanisms are determined as chalcogen 2H ↔ 1T sliding, cation shift, and commensurate lattice reconstructions, resulting in decreasing direct bandgaps and even a semiconductor–metal transition. These results will be a paradigm for the manipulation of multiphase heterostructures with controlled compositions and sharp interfaces, which will guide the future phase engineered electronics and optoelectronics of metal chalcogenides. Atomically resolved multiple 2D phase transformations (MoS2 → Mo4S6, MoSe2 → L‐, Z‐Mo6Se6) is observed in monolayer transition metal dichalcogenides under in situ heating with stoichiometry control by electron beam irradiation. Through chalcogen sliding and reconstruction mechanisms, phase transformations are well manipulated to fabricate diphase heterostructures with atomically sharp interfaces, which will pave the way to phase engineered optoelectronics.